Pengaruh Interaksi Orang Tua Terhadap Perkembangan Emosional Anak - Greatyvia Clarissa Rasyid (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study aims to analyze the influence of interaction between parents on children's emotional development. Using a descriptive-qualitative approach based on literature studies in the past five years, the study found that interactions that include communication, parenting, and emotional support play a very important role. These aspects contribute to the formation of the child's emotional regulation, self-confidence, and social skills. This study makes a significant conceptual contribution to the development of emotionally sensitive parenting strategies. Children who experience positive interactions in their family environment tend to show good emotional balance and adaptive social skills. Conversely, negative interaction patterns can trigger problems such as anxiety, aggressiveness, and difficulty socializing. In addition, factors such as parental stress, lack of understanding of emotions, and excessive use of technology play a role in affecting the quality of the relationship. The findings of this study emphasize the importance of parental involvement in emotionally aware parenting practices to support children's growth and development. The study also highlights the need for social support and ongoing education for parents, in order to build an emotionally healthy family environment. It is hoped that the results of this study can be the basis for the development of family education programs and parenting policies based on scientific approaches.